Minería, geografía y sociedad en el río Porce : Amalfi y Anorí entre 1850 y 1900 (2009)
ABSTRACT: The municipalities of Amalfi and Anorí were established on different sides of the Porce river in the north-east of the department of Antioquia in the early 19th century, and by the middle of the century they were important centers of regional development. New techniques of mineral extraction in both the alluvial and seam mining of gold during the second half of the century resulted in a significant increase in production, which in turn transformed the economic and social life of these localities. In the development of this local history, its physical characteristics and economic activities, the paper is based on primary sources such as denouncements and disputes related to the mines, periodicals and official publications of the time, and secondary sources dealing with the history of the places under study.